18x-7i=3(6x-7u)

Simple and best practice solution for 18x-7i=3(6x-7u) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18x-7i=3(6x-7u) equation:


Simplifying
18x + -7i = 3(6x + -7u)

Reorder the terms:
-7i + 18x = 3(6x + -7u)

Reorder the terms:
-7i + 18x = 3(-7u + 6x)
-7i + 18x = (-7u * 3 + 6x * 3)
-7i + 18x = (-21u + 18x)

Add '-18x' to each side of the equation.
-7i + 18x + -18x = -21u + 18x + -18x

Combine like terms: 18x + -18x = 0
-7i + 0 = -21u + 18x + -18x
-7i = -21u + 18x + -18x

Combine like terms: 18x + -18x = 0
-7i = -21u + 0
-7i = -21u

Solving
-7i = -21u

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Divide each side by '-7'.
i = 3u

Simplifying
i = 3u

See similar equations:

| 37x+50=9 | | 14x+4x^2=78 | | 14x+4x=78 | | 3z+6=4z^2+4z+1 | | 3(2-x)=3018 | | 2d+3=-10+d | | 2x^2+7x=39 | | 5c+5=4c+4 | | 200x=2x | | -10=-x-2y | | 3Q+4Q+2Q=108 | | -12=-2x-3x | | 6i(3i-9)= | | -2y=-3x-18 | | 5a^2+2-5a=0 | | 5y=-10+3y | | 15=3y-x | | -2y+4x=-8 | | 4x=6x-8 | | 9n-23=45 | | 15N-13=32 | | 2p+5=6+p | | 20=5y-4y | | x-1/3-2x-1/7-x-4/21=0 | | x/3+x+4/7=x-1 | | 5b=b+20 | | 24=7c-4c | | 7b=30+2b | | 5c+5=4+4 | | 7-(3x-(4x-5)-3)=0 | | 2r-5=r-3 | | 5c-4=4c-5 |

Equations solver categories